Evaluating nutritional yield pattern from diverse cropping systems to enhance nutritional security in the northwestern IGP of India - Bijarniya, Deepak; Prajapat, Kailash; Singh, Love K.; Jat, H.S.; Choudhary, Madhu; Sharma, Parbodh Chandler; Kalvania, Kailash C.; Yadav, Rajender Kumar; Jat, Mangi Lal; Krupnik, Timothy J.; Gathala, Mahesh K. (TAFSSA, 2024)
Limited dietary diversity in rural communities of the northwestern Indo-Gangetic Plain Zone (NWIGP) poses significant challenges to nutritional health and overall well-being. Many households primarily rely on staple crops, such as wheat and rice, resulting in a monotonous diet that lacks essential vitamins, minerals, and proteins. Consequently, malnutrition and micronutrient deficiencies—such as iron and vitamin A deficiencies—are prevalent in these communities, particularly among women and children. Severe acute malnutrition among preschool children has increased from 6.6% to 7.7%, putting these children at high risk (National Family Health Survey-3). To address these issues, an on-station research initiative was established in collaboration with the ICAR-Central Soil Salinity Research Institute (CSSRI) and the Transforming Agrifood Systems in South Asia (TAFSSA) Initiative under CIMMYT, focusing on enhancing nutritional diversity through the cultivation of diversified cropping system.